A Comparative Study on Changes in Total and Differential Milk Cell Counts, Activity, and Expression of Milk Phagocytes of Healthy and Mastitic Indigenous Sahiwal Cows - Alhussien, Mohanned Naif; Panda, Bibhudatta S. K.; Dang, Ajay Kumar (Frontiers in Veterinary Science, 2021)
Milk somatic cell counts (SCC) have been used as a gold standard to monitor mammary health as well as an indicator of raw milk quality. The present work was undertaken to compare the changes in the milk SCC, milk differential leucocyte counts (DLC), phagocytic activity (PA) of milk neutrophils and macrophages (by NBT assay), extracellular traps formation (Pico Green assay) and mRNA expression of various genes in milk neutrophils and macrophages (RT-PCR), and milk plasma cortisol concentration (ELISA) in healthy, subclinical (SCM), and clinical mastitis (CM) cows. Milk was collected from healthy, SCM, and CM cows grouped based on their SCCs and California mastitis test with 8 cows in each group. Milk SCC were estimated by SCC counter and DLC was done after staining the milk slide under a microscope at 100X. Total SCC in healthy, SCM, and CM cows were on an average of 128.30, 300.3, 694.40 ×103 cells/ml, respectively. Milk DLC indicated a lower percentage of macrophage and lymphocytes and a higher (p ˂ 0.05) percentage of neutrophils in SCM, and CM compared to healthy milk. The percentage of mature segmented neutrophils were lower, whereas immature band neutrophils were higher (p ˂ 0.05) in SCM and CM groups as compared to healthy cows. The viability, in vitro PA, and extracellular traps formation of neutrophils were lower (p ˂ 0.05) in SCM and CM milk samples as compared to healthy samples. However, the PA of macrophage remained unchanged in all the studied groups. The relative mRNA expression of toll-like receptors (TLR-2, TLR4), myeloperoxidase (MPO), and IL-2α receptor (CD25) were minimum in healthy samples and increased (p ˂ 0.05) with the progress of mammary inflammation. However, CD44 decreased (p ˂ 0.05) and CD62L remained unchanged in mastitis as compared to healthy cows. Plasma cortisol concentrations were higher (p ˂0.05) in mastitis as compared to healthy cows and were negatively correlated with the number of milk macrophages and the functions of milk phagocytes. Estimation of total SCC, milk DLC, and activity of milk phagocytes is essential for effective control and prevention of incidence of mastitis in dairy cows.